PEMILIHAN TIPE MOTOR BAGI PESAWAT ANGKUT SIPIL DAN PESAWAT MILITER - Wiradisuria, Djakaria (Mesin, 2003)
Since the begining of the first world war, the development and production of aircraft, especiallythe aircraft engine is booming, due to the urgent need of several leading countries to compete and gain superiority in the air for its survival and also to achieve hegemony politically as well as in the field of economy.World aircraft and engine producer were all involved in this competition, supported by its national - research - industrial and technological as well as high education centers. Many engine types, with various technological - level and specification is now available in the world market. For the customer it is a necessity to evaluate and select out of all those products the best choice to complete the airfleet which suits to the need from operational - economical - and logistic point of view.